Geophysical features influence the accumulation of beach debris on Caribbean islands. Issue 1 (15th August 2017) - Schmuck, Alexandra M.; Lavers, Jennifer L.; Stuckenbrock, Silke; Sharp, Paul B.; Bond, Alexander L.
Abstract: Anthropogenic beach debris was recorded during beach surveys of 24 Caribbean islands during April 2014–April 2016. Beach debris was classified according to material type (e.g., polystyrene) and item use (e.g., fishing). Geophysical features (substrate type, beach direction, and human accessibility) of sample sites were recorded in order to investigate their relationship with debris density. Results suggest the density of macro debris (items > 5 mm) is highest on uninhabited, sandy beaches facing a leeward direction. Higher debris quantities on inaccessible beaches may be due to less frequent beach clean ups. Frequently accessed beaches exhibited lower macro, but higher micro debris (items 1–5 mm) densities, possibly due to removal of macro debris during frequent beach clean ups. This suggests that while geophysical features have some influence on anthropogenic debris densities, high debris densities are occurring on all islands within the Caribbean region regardless of substrate, beach direction, or human accessibility. Highlights: Density of macro debris (> 5 mm) on Caribbean islands is highest on uninhabited, sandy beaches facing a leeward direction. Higher debris quantities on inaccessible beaches may be due to less frequent beach clean ups. The mean density of debris recorded in this study exceeds those reported by studies undertaken prior to 2000. Micro debris (1–5 mm) accounted for a significant proportion of the total number of items recorded on Caribbean beaches.